Associations between dietary intake, diet quality and depressive symptoms in youth: A systematic review of observational studies - Yiqi Wang; Jianghong Liu; Charlene Compher; Tanja V.E. Kral (Tabriz University of Medical Sciences, 2022)
Background: Depression is the third leading cause of worldwide disease burden among youth, and nutrition- and diet-related behaviors have been considered as an effective strategy for reducing the risk of depressive symptoms. This systematic review aims to examine associations between dietary intake and diet quality with depressive symptoms among youth. Methods: In this systematic review, a search of scientific articles published between 2000 and 2021 was performed in four databases (CINAHL, Embase, PsycInfo, and PubMed) according to the PRISMA checklist. After applying inclusion and exclusion criteria, observational studies that focused on associations between micronutrient, macronutrient, food group intake, and diet quality and depressive symptoms among youth, ages 3 to 18, were selected for review. Results: Thirty-two articles met the review criteria. Dietary intake of magnesium, vitamin B12, fiber, fruits, vegetables, and fish were consistently inversely related to depressive symptoms. However, the evidence of associations between intake of vitamins B6, C, D, and E, iron, copper, zinc, omega-3 fatty acids, carbohydrate, and dietary fat and depressive symptoms was mixed. Dietary effects on decreased depressive symptoms were more pronounced in children than adolescents. Additionally, most studies failed to adjust for potential confounding variables. Conclusion: This review provides preliminary and comprehensive evidence for a relationship between dietary intake, diet quality, and depressive symptoms in youth. Although the results are heterogeneous and more research is needed, our findings indicate the importance of nutrition interventions for youth for decreasing depressive symptoms or for preventing further symptom exacerbation.